Assessment of petroleum road tankers subject to rollover impacts - measurement and modelling - Hobbs, James; Stewart, Michael; Atkin, Chris; Richardson, Rob; Webb, Duncan (International journal of crashworthiness, 2023)
The UK Department for Transport (DfT) had observed that some petroleum road tankers contained defects in their circumferential welds, and these defects could increase the risk of failure during accidents. HSE SD were asked by the DfT to carry out rollover tests of tankers (topple tests) and predict the global impact response (assessment of weld failure was a separate piece of work and is not reported here). Two tankers containing the weld defects were obtained and topple tests were conducted. Predictions from the model were compared with pressure, strain and deformation measurements. In most comparisons good agreement was found between measurements and predictions. Once the model was verified by measurements with water as the payload in the topple tests it was revised to include fuel loads. This led to higher impact deformations (the reasons for this are discussed). This work has improved understanding of the response of these tankers in accident situations. The DfT have used the findings to assist UK Government Ministers' policy decisions regarding the non-compliant tankers.